2015
DOI: 10.14740/jocmr2284w
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Uncontrolled Anxiety Disorders Are Associated With the Increased Risk of Hypertensive Disorders in Japanese Pregnant Women

Abstract: BackgroundWe examined the risk of hypertensive disorders in relation to maternal depressive and anxiety disorders which were diagnosed before or during early pregnancy in Japanese women.MethodsWe reviewed the obstetric records of all Japanese singleton deliveries at ≥ 22 weeks’ gestation managed at the Japanese Red Cross Katsushika Maternity Hospital between 2009 and 2014. Potential risk factors for hypertensive disorders with maternal depressive and anxiety disorders were selected as follows: maternal age, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…Similar results were obtained in a recent study by Suzuki et al (2015). The authors observed heightened incidence of hypertension in pregnant women with a greater anxiety levels when compared to healthy controls.…”
Section: Numerous Epidemiological and Experimental Investigations Havesupporting
confidence: 89%
See 2 more Smart Citations
“…Similar results were obtained in a recent study by Suzuki et al (2015). The authors observed heightened incidence of hypertension in pregnant women with a greater anxiety levels when compared to healthy controls.…”
Section: Numerous Epidemiological and Experimental Investigations Havesupporting
confidence: 89%
“…Further, subjects in the GH group had significantly higher mean STAI-T scores, alluding to an association between trait anxiety and the development of gestational hypertension during the last trimester of pregnancy (Laken, Giblin, Lucas, & Sokol, 1986). Similar results were obtained in a recent study by Suzuki et al (2015). The authors observed heightened incidence of hypertension in pregnant women with a greater anxiety levels when compared to healthy controls.…”
Section: Numerous Epidemiological and Experimental Investigations Havesupporting
confidence: 83%
See 1 more Smart Citation
“…As HDP are diagnosed after 20 weeks' gestation, we next looked at the 17 studies that examined the onset/diagnosis of clinically significant symptoms or a diagnosis of depression mood or an anxiety disorder in pregnancy prior to 20 weeks' gestation (Avalos et al, 2015; Bandoli & Chambers, 2017; Catov et al, 2010; Cripe et al, 2011; De Vera & Bérard, 2012; Garza-Veloz et al, 2017; Goedhart et al, 2010; Henrichs et al, 2010; Ibanez et al, 2012; Kim et al, 2013; Kurki et al, 2000; Lang et al, 2019; Lutsiv et al, 2015; Palmsten et al, 2012; Suri et al, 2007; Suzuki, Shinmura, & Kato, 2015; Winkel et al, 2015) in order to determine if depression or anxiety preceded the diagnosis of HDP. Results of the analysis showed an increased risk of HDP in women who received a diagnosis or had self-reported clinically significant symptoms of depression or an anxiety in pregnancy before 20 weeks' gestation (RR = 1.27; 95% CI 1.07–1.50) 3…”
Section: Resultsmentioning
confidence: 99%
“…In a study of Vianna and her team, 35.6% of participants in a screening program for 90 pregnant women in 2017 reported having mild to severe anxiety [59]. Anxiety during pregnancy can raise the risk of developing gestational disorders, such as hypertension, especially in women who experience mild to severe anxiety as also results from other studies [59,60]. To offer emotional support throughout pregnancy, prenatal care should incorporate the mother's mental health follow-up services, given the significant morbidity and mortality linked to preeclampsia [61] It is well established that stress and anxiety are positively correlated, per the researches [62][63][64].…”
Section: Psychological Changes Stress and Anxiety Factors During Preg...mentioning
confidence: 83%